Manejo de insectos defoliadores asociados al cultivo de cannabis medicinal Cannabis sativa L, 1753. - León Moreira, Salma Dayana (2024)
Cannabis sativa L 1753, also called Indian hemp, is an annual herb grown mainly in Central Asia (India and China), defoliating insects are those that, in their larval or adult stages, eat the softer parts of the leaves, leaving holes in them, in the cultivation of C. sativa defoliating insects such as Lepidoptera being one of the pests that cause the greatest damage to C. sativa such as: the yellow woolly bear S. virginica, the Eurasian hemp moth G. delineana, the African asparagus caterpillar S. exigua, the armyworm H. zea, and the leaf miner L. Huidobrensis these cause damage to the crop by devouring its leaves, buds and flowers, the present work aims to analyze management alternatives for defoliating insects associated with the cultivation of C. sativa, its methodology is to gather information from current documents, research articles, virtual libraries and websites. The results obtained show that for the management of defoliating insects it is done through cultural, biological or chemical control methods. Cultural control includes keeping the area free of weeds, rotating the crop and using traps, biological control involves the use of other organisms such as entomopathogenic parasitoids and natural predators, as chemical control, pyrethroids, organophosphates or neonicotinoids should be used but it was concluded that integrated pest management is the best option for the management of defoliating insects because it reduces the negative effects of an approach and has many important benefits, such as the reduction to chemicals